THE PROFILE OF DIAGNOSTIC OF UNCATEGORIZED SYNDROME TREATED BY ISLAMIC SPECIFIC PRAYER IN NUR HIDAYAH HOSPITAL - Sagiran Sagiran; Tesaviani Kusumastiwi; Adang M.Gugun; Iman Permana (Publikasi Indonesia, 2023)
In daily practice, there are many patients that medically are not sick but suffer from illness. Those syndrome categories to be psychosomatic disorder (ICD 10). Islam believes about the power of an evil spirit. It can invade and attack a person caused illness. Physical exam and laboratory finding can be normal. They need islamic specific praying to relieve their suffering. The research design is a cross sectional study. Subjects in this study are patients at Nur Hidayah Hospital in 2014 - 2019 to whom receiving Islamic specific praying (ruqyah syar’iyyah). There are 369 patients treated by Islamic specific praying, but in the beginning, there is no standardized recording. The complete data of 22 patient are collected and statistically analyzed. The medical diagnosis of the subjects is: gastrointestinal disorders (10; 45%); cephalgia-epilepsy (5; 22%) anxiety disorders (4; 18%), sexual disorders (3; 13%). The reaction of treatment is vomiting, headache, heat sensation, and delirium. After those kinds of reaction, the patient relief from suffering and cure their illness. It is studied the diagnostic profile of Islamic specific praying in Nur Hidayah Hospital. Ruqyah Syar’iyyah can be used as complementary treatment